Engineering in plain sight : an illustrated field guide to the constructed environment - Hillhouse, Grady (No Starch Press, Inc., 2023)
"This illustrated book extends the field guide genre from natural phenomena to human-made structures, making their design and construction approachable and understandable to non-engineers. Readers will learn to identify characteristics of the electrical grid, roadways, railways, bridges, tunnels, waterways, and more"--